2009
DOI: 10.1103/physrevb.79.064524
|View full text |Cite
|
Sign up to set email alerts
|

Optimized single-qubit gates for Josephson phase qubits

Abstract: In a Josephson phase qubit the coherent manipulations of the computational states are achieved by modulating an applied ac current, typically in the microwave range. In this work we show that it is possible to find optimal modulations of the bias current to achieve high-fidelity gates. We apply quantum optimal control theory to determine the form of the pulses and study in details the case of a NOT-gate. To test the efficiency of the optimized pulses in an experimental setup, we also address the effect of poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Optimal control theory has also been applied to this problem [13,14,15], and recent work has indicated that arbitrarily fast control is possible using certain choices of pulses [16]. The presence of higher levels is also problematic for coupled qubit operation.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal control theory has also been applied to this problem [13,14,15], and recent work has indicated that arbitrarily fast control is possible using certain choices of pulses [16]. The presence of higher levels is also problematic for coupled qubit operation.…”
Section: Introductionmentioning
confidence: 99%
“…In quantum chemical, quantum optimal control made great success. Recent work has optimized the control law for closed or open system population transfer by using a gradient ascent pulse engineering algorithm [11,12]. Optimal control has been exploited to control the quantum decoherence, where an optimal control law was designed to effectively suppress decoherence effects in Markovian open quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…The controls we have at our disposal are collective controls of the lattice. The challenge is to control an ensemble of particles in parallel even though they each undergo a different quantum evolution, which mathematically is identical to the problem of robust control [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%